An uncommon localization of a giant hydatid cyst presenting with cardiac tamponade - İrfan Şahin; Berk Özkaynak; Burak Ayça; Ertuğrul Okuyan (KARE Publishing, 2015)
Cardiac involvement in hydatid cyst disease is a rare manifestation and may remain asymptomatic for years. The location of the cyst determines the presentation. In this report, we present a case of hydatid cyst presenting with massive pericardial effusion, right ventricle compression leading to cardiac tamponade. The diagnosis was established with transthoracic, transesophageal echocardiagraphy and computed tomography.